Parental Co‐Construction of 5‐ to 13‐Year‐Olds' Global Self‐Esteem Through Reminiscing About Past Events. Issue 6 (11th September 2017) - Harris, Michelle A.; Donnellan, M. B.; Guo, Jen; McAdams, Dan P.; Garnier‐Villarreal, Mauricio; Trzesniewski, Kali H.
Abstract : The current study explored parental processes associated with children's global self‐esteem development. Eighty 5‐ to 13‐year‐olds and one of their parents provided qualitative and quantitative data through questionnaires, open‐ended questions, and a laboratory‐based reminiscing task. Parents who included more explanations of emotions when writing about the lowest points in their lives were more likely to discuss explanations of emotions experienced in negative past events with their child, which was associated with child attachment security. Attachment was associated with concurrent self‐esteem, which predicted relative increases in self‐esteem 16 months later, on average. Finally, parent support also predicted residual increases in self‐esteem. Findings extend prior research by including younger ages and uncovering a process by which two theoretically relevant parenting behaviors impact self‐esteem development. Abstract : The title for this Special Section isOrigins of Children's Self‐Views, edited by Eddie Brummelman and Sander Thomaes